Model of a City Destination Card as a marketing tool of selected European cities - Drozdowska, Urszula; Duda-Seifert, Magdalena; Faron, Agnieszka (Management Sciences, 2018)
City tourism belongs to the strongest trends in the international tourism market, which is especially the case in Europe, where eight out of twenty largest city destinations are located. Faced with growing competition these urban destinations have, however, to look for new marketing solutions to strengthen their position and attractiveness for potential visitors. One of them is a destination card which integrates a variety of tourism services provided by several operators at a discounted inclusive price. Therefore, it offers visitors an advantage by bundling the products and services available without the need for booking and buying in advance. By doing so, the card also fosters higher participation in cultural activities and public transport usage and offers additional benefits for the city which can include spreading the tourist traffic throughout the city or attracting visitors to lesser known sites. Additionally, the destination card system can also provide data concerning tourist flows and allows to adapt the offer better to their specific needs. The purpose of this paper is therefore to work out the model of a city destination card for a large city. In order to achieve this objective, the top five European capital cities were selected based on the number of visitors. Subsequently, the comparative study – developed on the secondary analysis of data – of tourist cards offered in London, Paris, Rome, Prague and Vienna has been conducted. Based on the study and referring to the literature, the final results were formulated concerning the typical structure of a card and its additional elements, followed by the validity period solutions and their price. Satisfied customers highlight that the offered card combines everything needed for the tourist stay, as in their opinion, cards tend to be a very easy, convenient and simple way of sightseeing the city with benefits such as saving money and time. They also recommend longer periods of card validity. The value of the destination card as a marketing tool for a city has also been proven based on the appraisal of customers opinions
Management Sciences, 2018, vol. 23, no. 2, s. 19-28
Keywords: city tourism; European capital cities; destination card; tourism marketing; stolice europejskie; turystyczna karta miejska; turystyka miejska; marketing usług turystycznych